RESOLUSI KONFLIK BATAS-BATAS TANAH AKIBAT BENCANA TSUNAMI DI GAMPONG LAMDINGIN, KECAMATAN KUTA ALAM KOTA BANDA ACEH - Fathiah, Adha; Afrizal, Afrizal; Jendrius, Jendrius (JISPO : Jurnal Ilmu Sosial dan Ilmu Politik, 2019)
The Tsunami wave that occurred in Aceh in 2004 resulted in a shift in the joints of the social, economic and cultural life of the people. The tsunami left deep wounds and sadness for the victims left behind, the earthquake and tsunami disaster also destroyed infrastructure and various types of buildings, especially residential housing. One of the problems caused was the difficulty to find land boundaries that had been lost due to the disaster, this caused a conflict between Gampong residents who lived side by side. The study was conducted with a qualitative type descriptive approach and used Hugh Miall's theory which explained Conflict Resolution. The results of the study found that all conflicts that occurred in Lamdingin Village were resolved in local communities in Gampong through various conflict resolution processes. First, one party reports to the Keuchik or the Head of the Hamlet about the dispute that occurred, then the Keuchik invites the conflicting parties to be asked for information, then clarification of the object of the case is carried out, an internal meeting of the Gampong leader is held, and the last is the provisional decision to the parties fight.